Sistem Monitoring Kondisi Aliran Pada Gorong-gorong Saluran Air Menggunakan Metode Fuzzy - Moch. Alfian Zainullah; Dahnial Syauqy; Mochammad Hannats Hanafi Ichsan (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
Culverts are a water channel that is very beneficial for the environment in the community. With the culvert the public must be responsible to maintain well in order to avoid things that are not desirable like flooding due to clogged or overflowed. Clogged water channels because the people who often dispose of waste into culverts or other water channels so that plastic waste or organic waste clog water channels due to too much waste. Therefore, a blockage monitoring system was built on three aqueducts with each node using an ultrasonic PING sensor to measure the water level and the water flow G1 / 2 sensor to measure the rate of water velocity on the culvert. Data taken from the sensor will be processed by Arduino Nano microcontroller by using fuzzy method. Because the location of the culvert with a monitoring post is relatively far then the data processing will be sent using wireless NRF24L01, then LED RGB (Light Emitting Diode Red, Green, Blue) as output will produce conditions on the culvert with a red flame is stated danger, green declared alert and blue otherwise safe. in this study fuzzy method has been successfully applied on a system with 100% accuracy with average processing time of delivery is 1236, 1045 and 1133 millisecond.